KUALITAS PELAYANAN DIFABIS COFFE & TEA TERHADAP KEPUASAN PELANGGAN - Gray Nindyan Pradipta Mitya Utoyo; Kholis Azmi Mustofa; Lingga Yuliana (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The focus of this study is for investigating the impact of service quality on customer satisfaction in Difabis Coffee & Tea. The uniqueness of this study is the absence of case studies on coffee and tea disability with comparable characteristics in earlier references. Purposive sampling is the approach to sampling used in the research, which utilizes a quantitative descriptive methodology. Attendees to Difabis Coffee and Tea served as the study's respondent population. A total of 88 respondents participated in the data collection process in July 2023. The data used are first-hand records. The main information is obtained through surveys that were distributed using a Google form. Partial Least Square, utilizing Smart PLS 3.3.9, is the data analysis method used. The findings indicated a relationship between customer satisfaction and Difabis Coffee & Tea's service quality.